Poor Physical Capacity Combined With High Body Fat Percentage as an Independent Risk Factor for Incident Hypertension in Chinese Suburb-Dwelling Older Adults - Han, Peipei; Zhang, Yuanyuan; Chen, Xiaoyu; Liang, Zhenwen; Yu, Xing; Liu, Yuewen; Sang, Sijia; Mao, Jiayin; Liu, Jingxuan; Chen, Wuxiong; Li, Junxue; Cheng, Yazhou; et al. (Frontiers in Public Health, 2022)
BACKGROUND: This study was we examine the effects of poor physical capacity and high body fat percentage (BF%) on the incidence of hypertension in Chinese suburb-dwelling older adults. METHODS: This study was conducted on 368 Chinese suburb-dwelling participants aged ≥ 60 years without hypertension initially (mean age: 66.74 ± 5.59 years, 48.9% male). Poor physical capacity is defined by the Asian Working Group for Sarcopenia (AWGS) criteria as grip strength < 26 kg for men and < 18 kg for women or walking speed < 0.8 m/s. High BF% was defined as values greater than the upper tertile for body fat percentage as stratified by gender. The outcome was the incidence of hypertension. RESULTS: After the average follow-up duration of 2 years, the incidence of hypertension was 39.7%, and those experiencing poor physical capacity and high BF% had the highest incidence (81.0%). After multivariate adjustments, people suffering from only poor physical capacity (OR 1.11, 95% CI 0.55-2.25) or only high BF% (OR 1.37, 95% CI 0.80-2.34) did not develop new onset hypertension, while those with both poor physical capacity and high BF% had a significantly higher risk for incident hypertension (OR 6.43, 95% CI 1.91-21.64). CONCLUSION: In our study, we found the combination of poor physical capacity and high BF% may be more of an independent risk factor than poor physical capacity alone or high BF% alone, each of which did not have a significant effect on incident hypertension in Chinese suburb-dwelling older adults.